Near-neighbor tropical epiphytic orchids keep distinct mycorrhizal communities across their distribution in Costa Rica - Fernández Campos, Melania (2022)
Environmental and biotic axes act in combination to define the ecological niches of plant species. Two species with shared physical space are expected to compete for access to water and nutrients. In hyper-diverse areas like tropical forests, competition is expected to be extreme, and theory predicts that coexistence is only possible through specialization. In this study, two congeneric, epiphytic orchid species that colonize the same habitats and frequently live in close proximity (< 10 cm) across their distribution were chosen to test whether competition is reduced through orchid mycorrhizal fungi (OMF) specialization. The study was conducted in Costa Rica at 5 disparate locations where the two orchids, Masdevallia nidifica and M. chontalensis, co-occur to 1) assess niche partitioning through differences in OMF composition between the two species, and 2) analyze the OMF community composition of each species across elevation and forest types. We identified that the study species hosted significantly distinct communities of OMF when occurring alone and when in close proximity. Differences were partly driven by unique Serendipitaceae and Ceratobasidiaceae OTUs colonizing each orchid host. We also show that, with few exceptions, the two orchids maintain their non-overlapping and species-specific mycorrhizal associations across an elevation gradient and across forest types.